2018
DOI: 10.1093/abbs/gmy048
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of HGF against apoptosis in vascular endothelial cells caused by peripheral vascular injury

Abstract: Closed vascular injuries have danger of developing critical tissue ischemia with a high risk of amputation and limb loss. However, limited effective strategies exist at present. In this study, we investigate the role of hepatocyte growth factor (HGF) on apoptosis of vascular endothelial cells (VECs). First, apoptosis of VECs was induced by hypoxia treatment with or without HGF. Annexin V-7AAD apoptosis assay revealed that HGF overexpression significantly reduced VEC apoptosis. Then a closed peripheral vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…We also confirmed that HGF and SCF increased the expression of mitochondrial-associated proteins, Catalase and SOD2, via activation of the PI3K/AKT and ERK1/2 signaling pathways, which have anti-apoptotic roles and regulate the apoptosis-related proteins, Bcl and Bax [48]. HGF and SCF modulated the osteogenic differentiation of MSCs through the ERK1/2 signaling pathway [49,50], effectively promoting the timely removal of excessive ROS in cells, reducing mitochondrial damage, and delaying cellular senescence.…”
Section: Discussionsupporting
confidence: 69%
“…We also confirmed that HGF and SCF increased the expression of mitochondrial-associated proteins, Catalase and SOD2, via activation of the PI3K/AKT and ERK1/2 signaling pathways, which have anti-apoptotic roles and regulate the apoptosis-related proteins, Bcl and Bax [48]. HGF and SCF modulated the osteogenic differentiation of MSCs through the ERK1/2 signaling pathway [49,50], effectively promoting the timely removal of excessive ROS in cells, reducing mitochondrial damage, and delaying cellular senescence.…”
Section: Discussionsupporting
confidence: 69%
“…We also confirmed that HGF and SCF increased the expression of mitochondrial-associated proteins, Catalase and SOD2, via activation of the PI3K/AKT and ERK1/2 signaling pathways, which have antiapoptotic roles and regulate the apoptosis-related proteins, Bcl and Bax [38]. HGF and SCF modulated the osteogenic differentiation of MSCs through the ERK1/2 signaling pathway [39,40], effectively promoting the timely removal of excessive ROS in cells, reducing mitochondrial damage, and delaying cellular senescence.…”
Section: Discussionsupporting
confidence: 69%
“…It has been reported that treatment with H 2 O 2 induced upregulation of proapoptotic proteins, such as Bax, cleaved caspase, and cleaved PARP and downregulation of the anti‐apoptotic proteins, such as Bcl‐2 in MSCs . However, overexpression of HGF downregulated proapoptotic proteins and upregulated antiapoptotic proteins induced by hypoxia in vascular endothelial cells . Additionally, H 2 O 2 ‐induced apoptosis was mitigated by HGF in human embryonic stem cell derived‐neural progenitors .…”
Section: Discussionmentioning
confidence: 99%
“…30 However, overexpression of HGF downregulated proapoptotic proteins and upregulated antiapoptotic proteins induced by hypoxia in vascular endothelial cells. 31 Additionally, H 2 O 2 -induced apoptosis was mitigated by HGF in human embryonic stem cell derived-neural progenitors. 32 Previous studies have reported that treatment with HGF prevented H 2 O 2 -induced apoptosis.…”
Section: Interestingly H 2 O 2 -Induced Apoptosis Was Inhibited In Mmentioning
confidence: 99%